2015
DOI: 10.1093/nar/gkv1048
|View full text |Cite
|
Sign up to set email alerts
|

SIGNOR: a database of causal relationships between biological entities

Abstract: Assembly of large biochemical networks can be achieved by confronting new cell-specific experimental data with an interaction subspace constrained by prior literature evidence. The SIGnaling Network Open Resource, SIGNOR (available on line at http://signor.uniroma2.it), was developed to support such a strategy by providing a scaffold of prior experimental evidence of causal relationships between biological entities. The core of SIGNOR is a collection of approximately 12 000 manually-annotated causal relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
236
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(239 citation statements)
references
References 24 publications
(35 reference statements)
2
236
0
1
Order By: Relevance
“…Information gained from these databases allowed for the classification of proteins based on their molecular function, cellular compartment, associated biological pathways and protein-protein interactions, among other characteristics. For phosphorylation site analysis, several on-line programs were also available to explore further phosphorylation sites, related kinases, and associated networks, including Signor (42), Networkin/Kinforest (43), and PhosphoSitePlus (44). In particular, PhosphoSitePlus incorporates an expansive array of tools, such as motif searching and a sequence logo generator.…”
Section: Resultsmentioning
confidence: 99%
“…Information gained from these databases allowed for the classification of proteins based on their molecular function, cellular compartment, associated biological pathways and protein-protein interactions, among other characteristics. For phosphorylation site analysis, several on-line programs were also available to explore further phosphorylation sites, related kinases, and associated networks, including Signor (42), Networkin/Kinforest (43), and PhosphoSitePlus (44). In particular, PhosphoSitePlus incorporates an expansive array of tools, such as motif searching and a sequence logo generator.…”
Section: Resultsmentioning
confidence: 99%
“…Our work may be affected by the database of choice. To the best of our knowledge SignaLink 2 has the most straightforward pathway and cross-talk definition13 but our analysis should be tested in the future using other pathway curation sources like Reactome79 or Signor80. Information about cross-talk proteins is the determining factor in the analysis of other datasets because if a protein from a paralog group was involved in a cross-talk then the group was counted as a critical paralog group.…”
Section: Discussionmentioning
confidence: 99%
“…The three sources included the databases Signor (Perfetto et al , 2016), Signalink (Fazekas et al , 2013) and the functional directed interaction network defined by Wu et al (2010), who combined interactions reported in various databases, including Kegg (Kanehisa et al , 2017), Panther (Mi et al , 2017), NCI (Schaefer et al , 2009) and others, offering a large coverage of validated functional interactions. We also downloaded miRNA-gene interactions from miRTarBase (Chou et al , 2016), a database that contains experimentally validated interactions between miRNA and target genes.…”
Section: Methodsmentioning
confidence: 99%